Production of bioethanol from biomass waste (sugarcane) - Azrul Azmi, Yaziz (2006)
There are several methods to produce bioethanol. The bioethanol can be produced from cellulose and hemicelluloses that originate from many sources of biomass. The study was focus on the production of ethanol from sugarcane baggase using Saccharomyces cerevisiea as fermentation aide to expand the usage of the sugarcane baggase. The objectives of this study are to determine the yield of ethanol produced from certain amount of biomass waste (sugarcane baggase), the effects of the temperature and agitation speed in fermentation process. Pretreatment was used for breakdown the lignin seal to produce the highest yield of glucose. Enzymatic process is purposed to convert the cellulose to glucose. At the end of this study, the yield of ethanol produced was increase in a little with the temperature and agitation speed when reached the optimum point in fermentation process. Theoretically, every gram of glucose can theoretically yield 0.51 g of ethanol. The result given by the fermentation process where the ethanol composition at optimal temperature and agitation speed, 35oC and 200 rpm is 5.1 in weight percent and 6.5 in volume percent.